Methodology of the Process of Improving the Support Tools for Fuel and Energy Complex Within the Context of Achieving Energy Efficiency and Energy Independence of the Region - Ð¡hernyaev, Maxim; Grigorieva, Elena; Kreidenko, Tatiana; Rodionova, Irina (International Journal of Energy Economics and Policy, 2018)
This work is a continuation of a series of authors’ publications in the framework of a study of tools for supporting the fuel and energy complex in the context of achieving energy efficiency and energy independence of the regions. In this paper, the definition of the term "state support of the fuel and energy complex" was formulated, an analysis of state programs for supporting federal and regional levels in the fuel and energy complex was made. A consistent methodological scheme has been developed for organizing the process of improving the instruments for supporting the fuel and energy complex of the region, according to the specifics of the development of the fuel and energy complex and its role in the region’s economy. Keywords: instruments of fuel and energy complex support, regional fuel and energy complex, energy efficiency, energy independence of regions. JEL Classification: O13 DOI: https://doi.org/10.32479/ijeep.6970